EP362 Survival rate comparisons in open versus laparoscopic approach in early stage cervical cancer patients treated in Kielce cancer center: a single institution experience. (1st November 2019) - Misiek, M; Zalewski, K; Fras, P; Wrona-Cyranowska, A; Gieroń, B; Jedliński, M; Kopczyński, J; Koźmińska, M; Góźdź, S
Abstract : Introduction/Background: The purpose of this retrospective study was to assess the 5-year survival outcomes of cervical cancer patients who underwent an open radical hysterectomy (ORH) or laparoscopic radical hysterectomy (LRH) after its introduction in our center for the treatment of this disease. Methodology: We conducted a retrospective review of cervical cancer patients managed in Kielce Oncology Center, Poland with an ORH or LRH between 2011 and 2016. Results: A total of 115 women with cervical carcinoma stage IB1 or IIA1 were included in the study. Eighty-eight patients were treated with ORH, 27 were managed via LRH based on surgeon preference. Clinical characteristics did not differ between groups. Duration of total surgery time was longer in patients with ORH compared with that in the LRH group (p<0.001) contrary to blood loss that was higher in the ORH group than in LRH (p<0.001). Kaplan-Meier survival analysis revealed a progression-free survival at 3 and 5 years (PFS) rate of 95.68% and 90.91% for the LRH group and 95.68% and 85.52% for the ORH group, respectively (p=0, 95). Overall survival at 5 years was 89.00% for the ORH group and 100% for the LRH group and 96.6% for the RRH patients (p=0.389). Conclusion: Results from this retrospective study suggest that introduction of a laparoscopic procedures in the surgical staging and treatment of cervical cancer patients did not have a detrimental effect on surgical or disease outcome, irrespective of operative approach. Disclosure: Nothing to disclose.